Secagem de raspas da entrecasca do juazeiro (Ziziphus joazeiro Mart.) em camada de espuma (foam-mat drying) - Moreira, Mariana Fortini (2021)
The Juazeiro (Ziziphus joazeiro Mart.) is a plant belonging to the Rhamnaceae family, characteristic of the semiarid region of the Northeast, being the most notable representative of the Caatinga. It is known by several names such as, juá, joazeiro, juazeiro, among others. Its zest has several applications, due to its soapy properties, it can replace soap in places where the water is brackish and hard. It is also used in folk medicine, and the tea from its shavings and leaves is used for medicinal purposes. Like all plants, it is quite perishable, and one of the ways to make its conservation viable is drying; which deals with a process in which heat is supplied to a given material in order to evaporate the moisture content existing inside or on the surface of the material. Within the various methods, there is the foam-mat drying. The objective of this work is to obtain the powder from juazeiro’s bark by using foam-mat drying. The characterization of the juice and the foam was carried out through: density, total soluble solids content, hydrogen potential, stability, moisture and air incorporation. The drying kinetics were carried out based on a complete factorial experimental design 23 + 3 central points, where the input variables, agitation time, concentration of the bark in the foam and drying temperature were analyzed. The characterization of the final product was performed by determining: water solubility, hydrogen potential, total soluble solids content, water activity, and theoretical yield. The determination of saponins by the NMR spectroscopy method was performed, but no characteristic signs of saponins were found using the drying method in the bark of the juazeiro bark, showing good results.